Walkability Audit Tool for Commercial Streets in the Central Areas of GCC Cities: A Scoping Review - Alkrides, Bander Fahad B. (Journal of King Abdulaziz University: Environmental Design Sciences, 2026)
The walkability is an important and notable issue. There are several methods, but the walkability audit tool is one of the most effective. This paper offers a literature review of walkability audit tools that can be applied to commercial streets in the central areas of the cities in the Gulf Cooperation Council (GCC) region. This paper highlights important aspects of urban walkability, including functionality, safety, aesthetics, comfort, context, and applicability across various urban locations. This study uses the PRISMA technique to filter and review 30 contextual papers, categorising walkability factors into four domains and acknowledging diverse cultural, climatic, and context-specific factors in the GCC city context. The study implies the availability of a customisable and culturally appropriate walkability assessment instrument that will enhance the GCC region’s urban design and planning practices.